Odor Adsorption Kinetics on Modified Textile Materials Using Quartz Microbalance Technique - Sarıışık, Merih; Okur, Salih; Okur, Salih; Asma, Ş. (Polish Academy of Sciences, 2012)
In this study, a functional product with aromatic oil and vitamins for use at aromatherapy and spa centers or personal care has been designed to improve life quality of users by using multifunctional products with good odor, moisturizing, relaxation, anti-aging effects. For this purpose, commercial berry berry oil was capsulated in β-cyclodextrin, and then applied to 100% cotton towel fabric. Quartz crystal microbalance sensors were used to investigate odor adsorption kinetics on modified textile materials for the first time. The frequency responses vs. time plot shows clear linear step responses to the change in the concentration of odor molecules coming from the container filled with berry berry applied textile. The results also reveal that TiO 2 coated quartz crystal microbalance sensors can be used as e-nose to sense odor from textile coated with berry berry oil containing β-cyclodextrin capsules.
1st International Congress on Advances in Applied Physics and Materials Science (APMAS), Ankara, Turkey, 12-15 May, 2011
Keywords: Fruits; Aromatherapy; Adsorption kinetics; Textile materials; Quartz crystal microbalances